2019
DOI: 10.1108/pijpsm-01-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of job and family factors on work stress and engagement among Hong Kong police officers

Abstract: Purpose The purpose of this paper is to examine the effects of demands from three life domains: society, workplace and family and different resources at the individual, family and supervisor levels on occupational stress and work engagement among Hong Kong police officers. Design/methodology/approach A survey based on a random sample of 514 male and female police officers was conducted, and multivariate regression was employed to assess the effects of demands and resources on work stress and work engagement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 46 publications
(52 reference statements)
0
30
0
2
Order By: Relevance
“…As with all systematic reviews, new potentially eligible studies may have been published since the literature search was conducted, which could be a limitation. We have identified three studies that have been published since our search that examine organisational risk factors (shift work [36], job demands and resources [109] and supervisor support [125]) and mental health outcomes (stress [36, 125], EE and wellbeing [109]). The results of these studies are in agreement with the outcomes of our review [109, 125], and present a new significant association between shift work and occupational stress [36].…”
Section: Discussionmentioning
confidence: 99%
“…As with all systematic reviews, new potentially eligible studies may have been published since the literature search was conducted, which could be a limitation. We have identified three studies that have been published since our search that examine organisational risk factors (shift work [36], job demands and resources [109] and supervisor support [125]) and mental health outcomes (stress [36, 125], EE and wellbeing [109]). The results of these studies are in agreement with the outcomes of our review [109, 125], and present a new significant association between shift work and occupational stress [36].…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, this transition comprises a complex process associated with changes at both individual and work level. In support of this argument Li, Cheung, and Sun () have found that external factors such as job and family variables are important predictors of engagement levels among Asian police officers. Considering these findings, further longitudinal research is required to explore the transition from recruits to officers and implications for work engagement.…”
Section: Discussionmentioning
confidence: 92%
“…Antecedents of work stress can also come from organizational relationships with external parties, namely how the suitability of family demands versus organizational demands and between personal interests versus organizational policies. Some antecedents originating from organizational relationships with outsiders can be identified, namely family-role conflicts (Amirudin, 2019;Li et al, 2018), family role overload (Park and Jang, 2017), and work-life conflicts (Foy et al, 2018). In addition, job stress can be caused by career development, namely the career development environment (Naoum et al, 2018).…”
Section: Antecedents Of Work Stressmentioning
confidence: 99%
“…Research in the literature observed by the authors shows that work stress is studied in various types of work. Observations show that research on work stress is carried out in the construction professional profession (Ajayi et al, 2019;Hampton et al, 2019;Naoum et al, 2018), the police (Allison et al, 2019;Li et al, 2018;Nisar and Rasheed, 2019), teachers and headmaster (Heyder, 2019;Hu et al, 2019;Kongcharoen et al, 2019;Walker, 2020), Paramedics (Bjaalid, 2020;Duschek et al, 2019;Klein et al, 2019;Manoppo, 2020;Park et al, 2020;Rasool et al, 2020;Saadeh and Suifan, 2020;Zaghini et al, 2020), hotel industry employees (Goswani et al, 2019;Yousaf et al, 2020) and banking industry employees (Darte-Baah, 2019;Kashif et al, 2017;Oruh et al, 2020;Pandey, 2020;Parveen and Adeinat, 2019;Tripathi and Bharadwaja, 2018;Wu, 2020;). Some professions are only studied by one researcher, for example in the profession of daycare leader (Elomaa et al, 2020), library staff (Petek, 2018), the salesperson (Peaslay et al, 2020), women micro-entrepreneurs (Wijewardena et al., 2020), auditors (Amirudin, 2019), immigration officers (Yang et al, 2019), employees in the electricity sector (Sidhu et al, 2020), lecturers (Rafida, 2020), cabin crewmembers…”
Section: Types Of Work Researched In Research On Work Stressmentioning
confidence: 99%